DIGITAL TRANSFORMATION AND ITS IMPLICATIONS FOR THE FUNCTIONS OF BASIC EDUCATION MANAGEMENT: A LITERATURE REVIEW - Kasman, Kasman; Rahmat, Paisal; Nasution, Marlian Arif (Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Digital transformation in elementary education is influenced by culture and ways of thinking. Change often hinders elementary education institutions, both in terms of organizational culture and individual perspectives. New perspectives and methods in elementary education are necessary for digital transformation. The purpose of this article is to explain how digital transformation and its implementation impact management in elementary education, using a keyword search for “digital transformation in education.” The research findings reveal that digital transformation brings significant benefits in improving operational efficiency, enhancing data accessibility, and elevating the quality of services provided to various stakeholders. However, significant challenges and obstacles are also encountered along this transformation journey. Resistance to change, data security challenges, financial constraints, and a lack of technical skills are some of the aspects that need to be carefully addressed. Brough the development of robust policies, investment in data security, employee training, and effective management support, elementary schools can overcome these obstacles and maximize the benefits of digital transformation. In addition to facilitating the learning process, digital transformation has also become a strategic tool for planning, monitoring, and evaluating academic activities and management functions within educational institutions. While it has been implemented in various forms, its implementation remains inconsistent across educational institutions.